Genetic Diversity and Some Fruit Characteristics of Quince Genotypes Collected from Kayseri Region - Aydin Uzun; Ayşe Çil; Mehmet Yaman; Ömer Faruk Coşkun (Turkish Journal of Agriculture: Food Science and Technology)
Turkey with diverse ecologies harbours several plant and fruit species. Several species grow naturally are grown commercially. Kayseri and surroundings constitute natural spread zone of some fruit species. This study was conducted to determine genetic diversity and some pomological characteristics of 31 seed-propagated quince (Cydonia oblanga Mill.) genotypes. For pomological characteristics, fruit length, fruit width, water soluble dry matter (WSDM) and total acidity analyses were performed. Molecular analyses were conducted with the aid of 15 SRAP primer combinations. Genetic diversity in investigated genotypes varied between 0.53- 0.92 and genotypes were gathered under two main groups. Primer base lengths varied between 400- 1700 bp. A total of 97 clear bands were obtained and 91 of them were polymorphic (polymorphism ratio = 87.7%). Present findings revealed that existing quince populations of the region should be preserved and be used in further genetic studies.